Pengaruh Dampak Pandemi Covid 19 Terhadap Kegiatan Pelaku UMKM (Studi Kasus Kegiatan Pelaku UMKM Di Kabupaten Bogor – Jawa Barat) - Dedi Muliadi; Joko Setyawan (ITB AAS INDONESIA, 2023)
The Covid 19 pandemic had economic, social and political implications in almost all countries, including Indonesia. The economic impact of the Covid 19 pandemic had also been felt by the UMKM sector in Bogor Regency. The impact caused by this pandemic includes 5 aspects, namely 1) selling aspect. The average decline in selling of UMKM, 2) Business Revenue aspect. The average decrease in business revenue aspect, 3) Capital aspect. The number of UMKM experiencing capital problems increased, 4) The aspect of the number of employees. In this aspect, UMKM reduced the number of employees, and 5) The aspect of the ability to pay bank installments. Almost all UMKM (especially micro-entrepreneurs) experienced obstacles in carrying out their obligations to banks. This study also found that UMKM actors in Bogor Regency had implemented an online sales strategy, although not all of them. The number of UMKM implementing online strategies increased during Covid 19. The survival capacity of UMKM that made online sales was stronger than UMKM that only made offline sales Keywords : Impact of Covid-19, perpetrator UMKM